The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4038/sljid.v2i1.3321
|View full text |Cite
|
Sign up to set email alerts
|

Japanese encephalitis virus infection in an endemic area: hospital based study 1998 to 2000

Abstract: The Gampaha Deputy Provincial Director of Health Services (DPDHS) division reported a large number of Japanese encephalitis (JE) cases during 1996 to 1997. Notified cases included unconfirmed and confirmed cases. A study to determine the true disease burden was considered necessary. The proportion of undifferentiated fever cases due to Japanese encephalitis virus (JEV) varies in different populations and the Sri Lankan situation is not known. The objectives were to determine the proportion of undifferentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The JE has occurred in Sri Lanka for decades, seriously threatening human life since 1980 [ 21 ]. Gampaha was one of the districts that had reported a relatively large number of JE cases in the past [ 24 ]. The success of the immunization against JE in Sri Lanka is reflected in the fact that since 1988, the incidence of JE has decreased drastically with the increased coverage of immunization.…”
Section: Introductionmentioning
confidence: 99%
“…The JE has occurred in Sri Lanka for decades, seriously threatening human life since 1980 [ 21 ]. Gampaha was one of the districts that had reported a relatively large number of JE cases in the past [ 24 ]. The success of the immunization against JE in Sri Lanka is reflected in the fact that since 1988, the incidence of JE has decreased drastically with the increased coverage of immunization.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few studies on the aetiology of meningoencephalitis in Sri Lanka have been reported [Peiris et al, ; Peiris et al, ; Gunasekera et al, ; Karunarathne et al, ; Mori et al, ] due to limited diagnostic testing capabilities. Routine diagnostic services are available only for JEV by ELISA‐based IgM antibody detection in the public sector.…”
Section: Introductionmentioning
confidence: 99%
“…[3] One of the earliest studies performed in 1968 was able to isolate the Sri Lankan Japanese encephalitis virus (JEV). [4] The only virus that had been studied to some extent until recently was the JEV and it had been identified in some endemic areas: in the Western coastal belt up to the Northern Province. A study had identified varicella-zoster and its prevalence was 9%.…”
Section: Discussionmentioning
confidence: 99%